An enigmatic denarius of M. Herennius - Davis, Phillip (KOINON: The International Journal of Classical Numismatic Studies, 2019)
Michael Crawford in Roman Republican Coinage (Cambridge, 1974) from time to time notes varieties which lack control marks, on issues which normally include them on one or the other side; cf. for instance Crawford 364/1a, a denarius issue of Q. Antonius Balbus, struck in 83-82 BC on Crawford’s dating. These varieties can be distinguished by their rarity from issues like Crawford 363/1a-d, struck by L. Censorinus in 82 BC, in which substantial numbers of examples survive both marked and unmarked. This latter sort of differentiation is surely intentional on the part of the mint, the result of a deliberate choice by the moneyer or his agent (even if the reasons for this choice must remain opaque to us,) while cases like 364/1a seem appropriately described as mules, mint errors of a sort, the production of which was promptly stopped after discovery.